Clinical pattern and prevalence of rheumatic diseases among adults: a community-based cross-sectional study in rural Gadchiroli, India - Vinay R Joshi; Anand A Bang; Shekhar Y Bhojraj; Mahesh Deshmukh; Tushar Yarmal; Sameer Kalkotwar; Raghu Varma; Yogeshwar V Kalkonde; Abhay T Bang (Inishmore Laser Scientific Publishing Ltd, 2021)
# Background Population-level information on the prevalence of rheumatic disorders from rural India is rare. We investigated the prevalence and patterns of rheumatic disorders among adults in rural Gadchiroli, India. # Methods In this population-based, cross-sectional study, trained surveyors conducted a door-to-door survey to identify individuals with pain in back and extremities in two randomly selected villages from this region. Subjects who reported the presence of pain were evaluated by a team of a rheumatologist and orthopedic surgeons in a special clinic organized in these villages. # Results Out of 2,535 eligible adults, 2,259 (89%) were surveyed, and 1,247 (55%) reported pain in the back or the extremities, and were therefore referred to the specialist clinic. Out of 884 (71%) participants who attended the clinics, 615 (70%) reported pain in the extremities. The point prevalence of soft tissue rheumatism (STR) in the community was 28% (95% confidence interval, CI=26.1-29.8%) while that of arthritis was 12.2% (10.8-13.5). The point prevalence of rheumatoid arthritis was 0.4% (0.1-0.6). Both STR and arthritis were more common in women and in the elderly. # Conclusions Soft tissue rheumatism was the commonest rheumatic disorder in this rural community, followed by arthritis. Inflammatory and infectious disorders were rare. Given the high prevalence of STR and arthritis, community health workers and physicians working in rural areas need to be trained, in order to improve the management of these conditions.